Attention deficit hyperactivity disorder medications in children with heart disease. Issue 5 (October 2016) - Berger, Stuart
Abstract : Purpose of review: Attention deficit hyperactivity disorder (ADHD) is quite common in the general pediatric population, Its incidence is thought to be even higher in the population of patients with congenital heart disease, especially in those patients with complex disease and who have had cardiac surgical interventions early in life. There has been controversy as to the safety of ADHD medications, especially in the latter population of patients. This compendium is meant to review the effects of the ADHD medications and the safety of these medications in patients with either known or undiagnosed congenital heart disease. Recent findings: The concern with regard to the use of ADHD medications has been as a result of the reports of sudden unexpected deaths among patients taking stimulant drugs for ADHD. Therefore, the question of whether or not stimulant drugs increase the risk of adverse cardiovascular events has led to a discussion of the appropriate use of these drugs in patients with known cardiovascular disease, as well as a discussion as to the appropriate evaluation in order to identify undiagnosed 'at-risk' patients with congenital heart disease or arrhythmias. This article will review and amplify these discussions, as well as the conclusions that have come forth as a result of these discussions. Summary: Currently available data suggest that there is no evidence for serious adverse cardiovascular complications in children with known cardiovascular diseases including patients of congenital heart disease who are treated with stimulant medications. Despite this, if the patient does have known cardiac disease, or if the history and physical examination is suggestive of cardiac disease, it is suggested that consultation/evaluation with a pediatric cardiologist occur. It is extremely unlikely that stimulant medications would be contraindicated in almost any condition that falls under this category. However, a few specific cardiac conditions might tailor the choice of the specific ADHD medication. Therefore the coordination of care between the primary care physician, the ADHD medication-prescribing physician, and the pediatric cardiologist may be very important in this circumstance.